PENGEMBANGAN USAHA KELOMPOK PERAJIN TEMPE DI KECAMATAN CANDI KABUPATEN SIDOARJO (Jurnal Teknologi Pangan, 2015)
ABSTRACT   There are 500 artisans of tempeh in  Sepande village, subdistrict Sidoarjo, but it was not incorporated as a member of the Primary Cooperative Producers of Tofu- Tempeh Indonesia (PRIMKOPTI) "KaryaMulya".It was only 273 artisans e.i : 266 artisans of tempeh and 7 artisans of tofu. Nowadays the members of PRIMKOPTI only knowing how to processed of  tempeh by empirical procedure. Sometimes they made tempeh with additional stuff like corn, dry waste rice  and tapioca flour. The tempehthey produced, was sold to suitable buyer segment. Therefore they need a new breakthrough with more innovative ways to produce tempeh, because they were located at strategic area and hav e a good prospect to be developed. The objectives of community service program is to give training to groups of tempeh producers in using appropriate technology (TTG) such asusing tempeh slicer machine, training on good product packaging, management and marketing of product, and  provide training toproduct innovation e.i: the processed burger of tempeh.The methods of community service program were used in this activity are giving of knowledge (by communication, information, and education), practicing and mentoring to groups of tempeh producers. The results showed that the community service group being skilled in operatingtempeh slicer machine that previously was done manually, the increase of tempeh chip products and supported by the packaging design which have had the license under departement of health.The computerized of cooperative management arrangement gave a positive effect on the service to the cooperation members and the local community. The progress of the program indicated that tempe producers insight to process burger tempeh has increased drastically. Methods of mentoring can provide impact in increasing the income of tempeh producersgroup. Keywords :Enterprise development tempeh producers, TTG slicer of tempeh, packaging, burger of tempeh ABSTRAK Ada sejumlah 500  perajin tempe yang berada di desa Sepande kecamatan Candi kabupaten Sidoarjo akan tetapi yang tergabung sebagai anggota dalam Primer Koperasi Produsen Tahu Tempe Indonesia (PRIMKOPTI) ”Karya Mulya” hanya 273 perajin, dengan rincian 266 perajin tempe 7 perajin tahu.Selama ini anggota PRIMKOPTI hanya mengetahui cara pengolahan tempe saja yang sifatnya turun temurun, kadangkala mereka membuat tempe dengan campuran jagung, karak dan tepung tapioka, tempe yang dihasilkan dijual sesuai segmen pembeli. Oleh karena itu perlu adanya terobosan baru yang lebih inovatif mengingat di daerah perajin tempe sangat strategis untuk dikembangkan. Sehingga pada program pengabdian masyarakat ini bertujuan untuk melatih kelompok perajin tempe dalam penggunaan teknologi tepat guna (TTG) berupa mesin alat pengiris tempe, pelatihan tentang teknologi pengemasan, manajemen dan pemasaran produk, sertamemberikan pelatihan pengolahan inovasi produk olahan tempe yaitu burger tempe. Metode pengabdian masyarakat yang digunakan dalam program ini yaitu metode ceramah, praktek dan pendampingan pada kelompok perajin tempe. Hasil pengabdian masyarakat menunjukkan bahwa kelompok perajin terampil dalam penggunaan alat pengiris tempe yang awalnya dilakukan secara manual, produk keripik tempe yang dihasilkan meningkat produksinya yang ditunjang dengan design kemasan yang telah memiliki ijin Depkes. Penataan manajemen koperasi secara komputerisasi memberikan pengaruh positif terhadap pelayanan anggota koperasi maupun masyarakat setempat.  Bertambahnya wawasan para kelompok perajin tempe dalam pengolahan burger tempe. Metode pendampingan dapat memberikan dampak dalam meningkatkan penghasilan kelompok perajin tempe. Kata kunci : Pengembangan usaha perajin tempe, TTG pengiris tempe, pengemasan, burger tempe